Repeat testing for congenital hypothyroidism in preterm infants is unnecessary with an appropriate thyroid stimulating hormone threshold. Issue 4 (5th February 2008) - Korada, M; Pearce, M S; Ward Platt, M P; Avis, E; Turner, S; Wastell, H; Cheetham, T
Abstract : Background: Revised UK neonatal screening guidelines recommend that a second blood sample for assay of thyroid stimulating hormone (TSH) be taken when preterm infants reach a postmenstrual age of 36 weeks. Objective: To examine the results of a regional screening programme to see whether a rise in TSH concentration was observed in some preterm infants between the first sample taken around 5 days after delivery and the second sample taken at around 36 weeks. Methods: Whole-blood TSH concentrations in preterm infants born over a 2-year period (April 2005 to March 2007) were assessed, and the number of infants in whom there was a fall or rise to values below or above the local screening threshold (6 mU/l) was determined. Results: Baseline TSH samples were obtained from 2238 preterm infants (median gestational age 32 weeks, range 21–35) with second samples obtained from 2039 (median gestational 32 weeks, range 23–35). In 19 infants, TSH concentrations fell from above to below the screening threshold, and in five infants values rose from below the screening threshold to 6–10 mU/l. However, TSH concentrations fell to <6 mU/l on a further blood spot in four of these infants, and the remaining infant had a serum TSH of 6.8 mU/l. Three infants had raised TSH concentrations on both occasions with unequivocal hypothyroidism (serum TSH >80 mU/l). The initial TSH concentration in one of these infants was 6–10 mU/l. Conclusions: No infant with a normal TSH concentration on first sampling had a TSH concentration that rose above 10 mU/l on second sampling, and no infants with a normal TSH concentration on first screening are receiving long-term thyroxine treatment. This study suggests that a second sample may not be necessary with a screening threshold of 6 mU/l.